Advance-purchase financing of projects with few buyers - Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
I investigate a simple model of advance-purchase contracts as a mode of financing costly projects. An entrepreneur has to meet some capital requirement in order to start production and sell the related good to a limited number of potential buyers who are privately informed about their willingness to pay. I find that advance-purchase arrangements enable more costly projects to be financed than traditional funding sources. The entrepreneur uses advance-purchase surcharges as a price discrimination device. However, the discriminatory power is limited by the problem of free-riding, which is exacerbated as the number of potential buyers increases.
Keywords: D42; G32; H41; L12; L26; O31; 330; pre-ordering; price discrimination; excludable public goods; monopolistic provision; crowdfunding; innovation and R&D